Blowing-Up Solutions of the Shallow Water Equations (Journal of Nonlinear Modeling and Analysis, 2025)
In the paper, we study the question about global unsolvability ofthe Kawahara and Kaup-Kupershmidt shallow water equations in a boundeddomain. For certain initial-boundary-value problems of the shallow-waterequations, we establish the necessary conditions for the existence of globalsolutions. The proof of the results is based on the nonlinear capacity method.In closing, we provide some examples.